Violência infantojuvenil e o território da escola: o bullying como analisador de processos de subjetivação contemporâneos - Barros, João Paulo Pereira (2014)
This is a research about one of the main kinds of infant-juvenile violence related to school routine nowadays: bullying. The argument is based on dialogues related to the field of Phylosophy of Difference. Its main goal was cartographying the bullying-dispositive as an analyzer of contemporary subjectivity processes. Its specific goals were: to problematize theorical and conceptual matters about school violence, articulating it to the reflection about institucionalization and the current situation of school; to undertake an arche-genalogical debate about bullying, analyzing its emergency conditions as a subcategory of violence; to analyze the ways of operation of the bullying-dispositive on school routine and its subjectivity effects. The cartography was designed in two moments: an arche-genealogy of the invention of category bullying and an intervention-research on how such a dispositive operates at school. The intervention-research happened between the years 2012 and 2013 in a school from Fortaleza, Brazil. Attended this research workers from the school; students from 12 to 15 years old and their families. In the intervention-research, as strategies to data outputs, it was used: participant observation and production of field diaries; semi-structured interview with school management; workshops with teachers and students; rounds of conversation with families of students. As results, it is pointed out that the category bullying is invented from displacements of scientific and media speeches. Such displacements are related to: the contemporary recovery of school territory, in the transition of a disciplinary society toward a control society; the recrudescence of a neoliberal ethos, as well as of the security dispositives and the contemporary ideia of risk; the policital shapes of difference nowadays. The intervention-research at school territory makes more complex the cartography of the bullying-dispositive, pointing out that it moves discourses that ratify naturalization processes and depolicization of school violence, in addition to the reissue of tensions between indiscipline and school violence. With regard to institutional practices for facing the peer violence, the highlights were the practices of surveillance and standardization sanction, such as warning, suspension, expulsion and expansion of electronic monitoring, in addition to "culture of peace" campaigns as bullying prevention strategy and medicalization practices as well as making school relations a judiciary issue. Thus, this study argues that the bullying-dispositive operates updates joints between discipline and biopolitics. Ratifying the heterogeneity of practices that cross the school, gaps and creepage distances are also highlighted in the case of these operating modes while individualizing and totalizing of the bullying-dispositive, in that, at school, there were deterritorializations and inventive movements that create common plans about the issue of infant-juvenile violences. The text concludes arguing that the bullying-dispositive, imported from other realities, is a new infant-juvenile standardization technology woven in the bulge of neoliberal arts of life government, and it is affiliated to contemporary retorical trends about diversity, wich, more than offer resistance to hegemonic subjectivity sahpes, consider the alteriry under the sign of stereotype and mask real mechanisms of social and educational exclusion. Opposed to this bias, the thesis indicates an ethical-aesthetic-political perspective concerning the infant-juvenil violences that vivify the school territory.